THE MODEL OF INTEGRATED ASSESSMENT OF TECHNOLOGICAL READINESS OF INNOVATIVE SCIENTIFIC AND TECHNOLOGICAL PROJECTS - A. V. Komarov; A. N. Petrov; A. V. Sartory (Ekonomika Nauki)
The article describes the model of integrated assessment of technological readiness of innovative scientific and technological projects, which is an integral part of the methodology of expert evaluation of projects. The model can be used both at the stage of selection of applications for project financing, and for creating tools for measuring the level of technological readiness of projects in the course of their implementation. The application of the proposed model will make it possible to formulate unified approaches and requirements to the formation of a system of criteria for the expert evaluation of innovative scientific and technological projects at various stages of their life cycle that can be used by various development institutions, and for project implementers –  to determine the degree of readiness of the results obtained for industrial implementation.